Gambaran Gangguan Menstruasi Pada Pengguna Kontrasepsi Hormonal Di PMB Yuli Arini Dan PMB Hj.Nani Sutiani Kecamatan Majenang - tofa123; Isnaeni Rofiqoch (2022)
Family Planning (KB) is one way to reduce the population explosion in Indonesia and to create a quality family, but it does not always have a good effect, because the use of KB, especially hormonal, has some side effects that are slightly detrimental for women who use it. . Therefore, this study wanted to know the description of menstrual disorders in hormonal family planning users in PMB Yuli Arini and PMB Hj. Nani Sutiani, Majenang sub-district, Cilacap Regency. The research method is quantitative research using descriptive methods and cross sectional approach methods. The population in this study were mothers who used hormonal family planning at PMB Yuli Arini and PMB Hj.Nani Sutiani, totaling 532 people with a sample of 84 people, analyzed by descriptive statistical analysis. The results showed that most users of hormonal contraception had irregular menstrual patterns as many as 82 respondents (97.6%), had a menstrual period of 1-2 days as many as 75 respondents (89.2%), had a slight bleeding volume as many as 83 respondents (98.8%), had a menstrual cycle menstruating amenorrhea as many as 71 respondents (84.6%) and experiencing spotting bleeding as many as 80 respondents (95.2%). The conclusion in this study was that the most menstrual disorders experienced by respondents were irregular menstruation (97.6%) and spotting bleeding (95.2%).